1998
DOI: 10.1006/mpev.1998.0513
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Nucleotide Sequence of the Domestic Dog (Canis familiaris) Mitochondrial Genome

Abstract: The complete nucleotide sequence of the mitochondrial genome of the domestic dog, Canis familiaris, was determined. The length of the sequence was 16,728 bp; however, the length was not absolute due to the variation (heteroplasmy) caused by differing numbers of the repetitive motif, 5Ј-GTACACGT(A/G)C-3Ј, in the control region. The genome organization, gene contents, and codon usage conformed to those of other mammalian mitochondrial genomes. Although its features were unknown, the ''CTAGA'' duplication event w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
0
9

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(180 citation statements)
references
References 63 publications
(90 reference statements)
4
163
0
9
Order By: Relevance
“…The base composition of the Tibetan Mastiff mtDNA is 28.7% T, 25.6% C, 31.6% A and 14.1% G. The AT content (60.3%) is significantly higher than the GC content (39.7%), which is consistent with the base composition of the mitochondrial genomes of other Canids (Kim et al, 1998;Arnason et al, 2006;Bjö rnerfeldt et al, 2006). Table 3 details the genes, their location and the length of the Tibetan Mastiff mitochondrial genome.…”
Section: Characteristics Of the Tibetan Mastiff Mitochondrial Genomesupporting
confidence: 61%
See 2 more Smart Citations
“…The base composition of the Tibetan Mastiff mtDNA is 28.7% T, 25.6% C, 31.6% A and 14.1% G. The AT content (60.3%) is significantly higher than the GC content (39.7%), which is consistent with the base composition of the mitochondrial genomes of other Canids (Kim et al, 1998;Arnason et al, 2006;Bjö rnerfeldt et al, 2006). Table 3 details the genes, their location and the length of the Tibetan Mastiff mitochondrial genome.…”
Section: Characteristics Of the Tibetan Mastiff Mitochondrial Genomesupporting
confidence: 61%
“…The genome uses four initiation codons: eight genes use ATG; NADH2, NADH3 and NADH5 use ATA; NADH6 uses AAT; and NADH4 uses GTG. The stop codons of 11 genes are complete termination codons (TAA, TAG or AGA) and four genes (COIII, NADH3, NADH4 and NADH6) use incomplete termination codons, as is seen in other Canids (Kim et al, 1998;Arnason et al, 2006;Bjö rnerfeldt et al, 2006). As in some other mammals, there are four overlapping reading frames in the Tibetan Mastiff, ATPase8/ATPase6, ATPase6/CoIII, NADH4/NADH4L and NADH5/NADH6, which overlap by 43, 1, 7 and 15 bp, respectively (Table 3).…”
Section: Protein-coding Genesmentioning
confidence: 85%
See 1 more Smart Citation
“…Intergeneric, interfamily, and interorder phylogenies have been studied using the 12S and 16S rRNA gene sequences Hay et al, 1995;Titus and Larson, 1995;Ruvinsky and Maxson, 1996;Moore, 1996, 1998;Kobel et al, 1998). On the other hand, the homologies or differences of each mitochondrial gene or D-loop region have been recently reported among several related animal species based on the complete nucleotide sequences of mitochondrial genomes (Giorgi et al, 1996;Lopez et al, 1996;Xu et al, 1996;Härlid et al, 1997;Kim et al, 1998;Sumida et al, in preparation). These studies showed that the degrees of homologies between mtDNAs varied according to the individual genes.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity and quality of PCR products were evaluated using Picodrop (Picodrop Limited, Saffron Walden, UK). Purified PCR products (660 base pair length) were sequenced with BigDye ® Terminator v. Kim et al (1998).…”
Section: Methodsmentioning
confidence: 99%